Aching desolation: Liverpool prison and the regressive limits of penal reform in England and Wales. (30th March 2019) - Sim, Joe
Abstract : This article explores the current penal crisis through a case study of Liverpool prison, and the appalling nature of the prison's regime, as documented in January 2018 by HM Inspectorate of Prisons. The dehumanising nature of the regime was not unique as a number of other prisons inspected during 2018 were also shown to be seriously detrimental to the health and safety of prisoners. The article also explores the problematic nature of the state's response to the crisis and the limitations of that response. This raises a number of theoretical and political questions about the abject failure over two centuries of liberal reform. In turn, this failure raises questions about the future, beginning with recognising that the prison should be understood as an institution of the neoliberal state, which is oriented towards criminalising and controlling those on the economic and political margins of a deeply divided, fractured social order.